Blind encoding into qudits - Shamsul Shaari, Jesni; Wahiddin, Mohamed Ridza; Mancini, Stefano (Elsevier, 2008)
We consider the problem of encoding classical information into unknown qudit states belonging to any basis, of a maximal set of mutually unbiased bases, by one party and then decoding by another party who has perfect knowledge of the basis.Working with qudits of prime dimensions, we point out a no-go theorem that forbids ‘shift’ operations on arbitrary unknown states. We then provide the necessary conditions for reliable encoding/decoding.